Urban layout, industrial land usage and prevailing winds: risk confrontation in the city of Salamanca, Mexico - Pérez Crespo, José (Universidad de Boyacá, 2021)
he present article participates the reader to a reflect on the existing city of Salamanca in the Mexican Bajío region. The city’s sanitary conditions were implemented during its origins and its later territorial growth under the urban health criteria of the royal colonial ordinances, which were modelled on the methods of Vitruvian planning. Despite its benevolent principles in spatial configuration of the city’s functional and collective spaces, and the evolution of the settlement and its desire for progress, the city, in the second half of the 20th century, generated a national political-economic solvency, with a consequent need for occupation or use of industrial land. But this expansion was effected by only partially resolving and without a future vision regarding the behavior of emissions from petrochemical processes in the city refinery. Winds trajectories, over land originally destined for residential  services and functions had important consequences for the health of its population; in this present report, statistics obtained from monitoring content of chemical compounds in the last year (2019) along with certain with questionable information were considered; all indicators were used to study the risk confronting the urban layout, and the effects of hybrid land use and flow of industrial emissions, caused by winds flowing across the urban territory under this study.